Study of the Physical Aptitude Related to the Health and Corporal Composition in students of the primary and secondary level of the Experimental College of Application - UNE 2009 - Salinas Arias, Saulo (2011)
The main objectives of this dissertation are: (1) To identify and to describe the levels of Physical Aptitude Related to health, (2) To identify and to describe the characteristics of the Corporal Composition in the students of both sexes and (3) To determine the differences of the Physical Aptitude Associated with Health and Corporal Composition depending on the age, sex and shift of study. The design of the study was a descriptive comparative. There were studied 1173 students (569 F - 604 M) of the levels: primary and secondary between the 06 and 16 years old of the Experimental College of Application, Chosica - Peru. To evaluate the Physical Aptitude Related to Health there was chosen the battery of test FITNESSGRAM, whose results are interpreted in criteria terms and it is constituted by four tests: Curlp up, Push up, Trunk Lift and Career of the Mile. In the Corporal Composition they were determined across the index of corporal mass and the subcutaneous adiposity; it was established from the sum of three cutaneous folds of the triceps, subescapular and calf. The oily mass, lean mass and percentage of fat were evalu- ated taking the equations of Slaughter (1988) as a reference.